2001
DOI: 10.1007/s11906-001-0038-2
|View full text |Cite
|
Sign up to set email alerts
|

Hyperuricemia and renal function

Abstract: Increased serum urate concentration is commonly seen in clinical practice. It does not represent a specific disease, nor is it an indication for therapy. Hyperuricemia can be the consequence of increased uric acid production and/or decreased renal capacity to excrete uric acid. In essential hypertension, it has been described in up to one third of patients and is directly related to an increase in renal vascular resistance and inversely correlated with renal plasma flow. In other words, abnormal renal hemodyna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
28
1
8

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(39 citation statements)
references
References 64 publications
1
28
1
8
Order By: Relevance
“…Recent epidemiological evidence indicated that hyperuricemia might be a risk factor for renal dysfunction [43,44]. In accordance with the previous studies, the current study showed that fructose resulted in hyperuricemia and attenuated renal function manifested by increase in serum creatinine and urea.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Recent epidemiological evidence indicated that hyperuricemia might be a risk factor for renal dysfunction [43,44]. In accordance with the previous studies, the current study showed that fructose resulted in hyperuricemia and attenuated renal function manifested by increase in serum creatinine and urea.…”
Section: Discussionsupporting
confidence: 91%
“…Although the role of uric acid in the metabolism of triglycerides remains unknown, uric acid might be involved in either the overproduction or the reduction of clearance of triglycerides. A decrease in the clearance of triglycerides in fructose-fed rats has been attributed to a reduction in lipoprotein lipase activity in endothelial cells [44]. An alternative explanation is the possibility that the de novo increase in purine synthesis observed in fructose-fed rats may be pathogenetically linked to hepatic fatty acid synthesis, resulting in overproduction of triglycerides [46].…”
Section: Discussionmentioning
confidence: 99%
“…A population definition of hyperuricemia in men is an SUA Ͼ7.0 mg/dL, whereas a physical chemical definition of hyperuricemia is Ͼ6.5 mg/dL, as serum is supersaturated for monosodium urate at concentrations above this. 22 A SUA level Ͼ7.0 mg/dL (416 mol/L) was associated with a RR for hypertension of 1.36 (95% CI: 1.07 to 1.74) and 1.08 (95% CI: 0.83 to 1.39) in age-adjusted and multivariable-adjusted analyses, respectively. A SUA level Ͼ6.5 mg/dL (387 mol/L) was associated with an RR for hypertension of 1.34 (95% CI: 1.16 to 1.55) and 1.25 (95% CI: 1.08 to 1.45) in age-adjusted and multivariable-adjusted analyses, respectively.…”
Section: Resultsmentioning
confidence: 93%
“…PbAC could increase blood urea by more than one mechanism, including enhancement of proteins catabolism, conversion of ammonia to urea by induction of arginase-enzyme synthesis [33] , and inhibition of amino acids incorporation in proteins [34] . The hyperuricemia induced by PbAc treatment might result from over-production and/or reduced renal excretion of uric acid [35] , and elevation of endogenous oxygen species levels [36] . Co-treatment with BV extract inhibited PbAc-induced nephrotoxicity, as indicated by significant restoration of serum creatinine, urea and uric acid.…”
Section: Resultsmentioning
confidence: 99%